2022
DOI: 10.1210/endocr/bqac102
|View full text |Cite
|
Sign up to set email alerts
|

Mitotane Targets Lipid Droplets to Induce Lipolysis in Adrenocortical Carcinoma

Abstract: Introduction Adrenocortical Carcinoma (ACC) is a rare aggressive cancer with low overall survival. Adjuvant mitotane improves survival but is limited by poor response rates and resistance. Mitotane’s efficacy is attributed to the accumulation of toxic free-cholesterol, predominantly through cholesterol storage inhibition. However, targeting this pathway has proven unsuccessful. We hypothesize that mitotane-induced free-cholesterol accumulation is also mediated through enhanced breakdown of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…A total of 1612 genes were differentially expressed (|logFoldChange| ≥ 1.5, P<0.05) between responder and non-responder tumors ( Figure 3B ). Evidence has accumulated that mitotane dysregulated lipid metabolism and raised the potential correlation between mitotane responsiveness and capacity of handling lipids ( 37 , 38 ). From our transcriptome data, to be noted, expression of genes involved in steroidogenesis ( CYP11B1 ) and lipid metabolism ( CYP27A1, ABCA1, PLIN2, PLIN4, NR1H3 , etc) were significantly upregulated in mitotane-sensitive tumors ( Figure 3C ), implying elevated capacity for handling intracellular lipids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1612 genes were differentially expressed (|logFoldChange| ≥ 1.5, P<0.05) between responder and non-responder tumors ( Figure 3B ). Evidence has accumulated that mitotane dysregulated lipid metabolism and raised the potential correlation between mitotane responsiveness and capacity of handling lipids ( 37 , 38 ). From our transcriptome data, to be noted, expression of genes involved in steroidogenesis ( CYP11B1 ) and lipid metabolism ( CYP27A1, ABCA1, PLIN2, PLIN4, NR1H3 , etc) were significantly upregulated in mitotane-sensitive tumors ( Figure 3C ), implying elevated capacity for handling intracellular lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Oxysterol/LXR involves in adrenal steroidogenesis and serves as a safety valve to limit free cholesterol levels, thereby protecting adrenal cortex from lipotoxicity ( 48 ). Because mitotane could cause lipotoxicity in ACC cells through targeting lipolysis and cholesterol storage ( 19 , 38 ), we hypothesize that ACCs expressing higher level of CYP27A1 and ABCA1 might tightly depend on its capacity of handling cholesterol flux, thus vulnerable to disturbance of lipid homeostasis induced by mitotane.…”
Section: Discussionmentioning
confidence: 99%
“…Warde et al recently showed that mitotane sensitivity correlates with intracellular lipid content; while MUC-1 and H295R cells store similar amounts of intracellular lipid droplets, MUC-1 (mitotane resistant) cells are rich in triacylglycerols, whereas H295R (mitotane sensitive) cells are rich in cholesterol esters [77]. Lipid content as measured by Hounsfield units is used in some diagnostic algorithms for ACC; however, these results show that further distinguishing the particular lipids involved may provide more useful clinical information [78,79].…”
Section: Cell Linesmentioning
confidence: 99%